ALIENASI TOKOH UTAMA DALAM NOVEL POL KARYA PUTU WIJAYA - Anwar Efendi (LITERA, 2005)
This research objective is to describe two things, namely (1) the manifestations ofalienation and (2) characterization elements employed to describe human alienationin Pol, a novel by Putu Wijaya. These two things are related to the worldview adoptedby Putu Wijaya as a writer in response to the sociohistoricalcondition in society.The source of the data in this study was Putu Wijaya’s Pol (the first impression,1987). The data were collected through reading and recording. The data analysiscovered two aspects, namely (1) the structural aspect, and (2) the genetic aspect of theliterary work, the writer’s worldview. The validity was assessed through semanticvalidity and the reliability was assessed by reading and rereading (intraraterreliability).On the basis of the research findings and analysis, some inferences can be made.First, alienation in Pol on the basis of its manifestations can be classified into threecategories, namely (a) loneliness, (b) spiritual emptiness, and (c) disappointment.Second, characters’ alienation symptoms are expressed through characterizationelements, comprising (a) the writer’ s description of characters, (b) characters’thoughts, (c) characters’ actions, and (d) minor characters’ reactions to the maincharacter. A literary work as a life model or an alternative world is always relatedto the real life. In the novel, Putu Wijaya posits himself as a photographer of thesociety’s life.